To substitute the value of y from the first equation (-x-4) into the second equation, we replace y with -x-4 in the second equation:
3x + (-x - 4) = 8
Combining like terms, we get:
2x - 4 = 8
Adding 4 to both sides:
2x = 12
Now, divide both sides by 2:
x = 6
Therefore, the correct option is x = 6.
From the following system of equations, create a new equation by substituting the value of y from the first equation into the second equation.
From the new equation, evaluate the value of x.
y = - x - 4
3x + y = 8
Choose the correct option
(1 point)
x = 8
x = 12
x = 6
x = 3
1 answer